2021
DOI: 10.3389/fenvs.2021.618198
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urban Green Space in Promoting Inclusion: Experiences From the Netherlands

Abstract: Urban Green Space (UGS) is considered to be beneficial for health and wellbeing of urban residents. But there is growing evidence that benefits are not equally distributed. In this article we aim to understand the role that UGS plays in the process of social exclusion and the role urban greening strategies can play in enhancing social equity for specific groups that are excluded: elderly people with dementia, people with mental issues and people from an underprivileged neighborhood. The concepts of inclusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…During the pandemic, researchers have found that park use increased when parks were open [2,3,18,[32][33][34][35][36][37][38][39][40] and residents reported that these spaces improved their mental health [38,40]. These spaces have long been known to provide humans with multiple ecosystem services in addition to wellness, including mental health [7,13,22], climate regulation [41], and cultural benefits [42].…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, researchers have found that park use increased when parks were open [2,3,18,[32][33][34][35][36][37][38][39][40] and residents reported that these spaces improved their mental health [38,40]. These spaces have long been known to provide humans with multiple ecosystem services in addition to wellness, including mental health [7,13,22], climate regulation [41], and cultural benefits [42].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusive design is the ongoing process of designing solutions to accommodate the viewpoints, experiences, and situations of people that were not accommodated before (Levanier, 2021). In the cities of today, inclusion shares an intense relationship with its opposite term: exclusion (De Haas et al, 2021). Therefore, anyone working on inclusive green design will encounter obstacles of old designs that were based on exclusion from dated philosophies and ideologies.…”
Section: Discussionmentioning
confidence: 99%
“…In short: equality refers to equal measures, despite the outcome; equity refers to a fair outcome that does not have to be equal. For instance, for health reasons, an equity approach would promote measures such as green space, healthcare, and social work in deprived neighbourhoods, while an equality approach would provide each neighbourhood with the same number of measures (De Haas et al, 2021). Nonetheless, inclusive design requires both equitable and equal approaches.…”
Section: Three Building Blocks For Inclusive Designmentioning
confidence: 99%
“…A brief analysis of previous research demonstrates the considerable attention to studying the specific aspects of the green areas functioning. Much attention is paid to the study of certain aspects of sustainable urban development, including the planning structure of cities and the importance of recreational areas (Morar et al, 2016;Morar et al, 2019;Wolff and Haase, 2019;Snep et al, 2020;Morar et al, 2021a;Morar et al, 2021b;De Haas and Hassinkstuiver., 2021;Guenat et al, 2021;Rostang et al, 2021), implementation of the development strategies of Ukraine's regions ), and regional development on the whole (Niemets et al, 2019c). In particular, Barrera et al (2016) considered UGAs from the standpoint of the environmental framework of the territory.…”
Section: Introductionmentioning
confidence: 99%